EFFECT OF DIFFERENT FEEDING LEVELS ON PHYSICO-CHEMICAL TRAITS FOR MAIN CARCASS CUTS OF PEKIN DUCKS IN KURDISTAN REGION OF IRAQ - Azad Sh. S. Al-Dabbagh; Sardar. Y. T. Al- Sardary (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The objective of this study was to investigate the effect of different feeding levels (0%, 25%, and 50%) of alfalfa pellet ration (APR) (47% alfalfa) on the main carcass cuts Physico-chemical traits of Pekin ducks (Anas platyrhynchos). A total of 270 one-day-old ducklings were used. The birds at seven-day-old were assigned to 9 indoor pens of (2.2×1m) with outdoor and swimming pool (9.8×1m). Each pen represented an indoor replicate with 30 ducklings. The feeding program for Pekin Duck group treatments with (APR) (47% alfalfa) was used as a replacement to the basal diet at different percentages (0%, 25%, and 50%) for control (T0), first (T1) and second (T2) groups, respectively. At the end of the rearing period at 49 days, 6 birds (3male+3female) were randomly selected from each treatment, slaughtered and each breast and thigh muscle were excised for meat quality analysis. The results showed that treatments and sex did not significantly influence meat Cholesterol content, and most results for each of cooking loss, color, pH, chemical composition, and amino acid profile of the meat. In contrast, the treatments and sex had a significant effect on most for each fat-soluble vitamins, water-soluble vitamins, and fatty acid profiles. In general, feeding ducks with a 25% of APR improved the color of breast, and fat-soluble vitamins with Cholesterol in both breast and thigh muscle while feeding ducks with a 50% APR improved most Physico-chemical traits.